Supramolecular Structure and Functional Analysis of the Type III Secretion System in Pseudomonas fluorescens 2P24 - Liu, Ping; Zhang, Wei; Zhang, Li-Qun; Liu, Xingzhong; Wei, Hai-Lei (Frontiers in Plant Science, 2016)
The type III secretion system (T3SS) of plant and animal bacterial pathogens directs the secretion and injection of proteins into host cells. Some homologous genes of T3SS were found also in nonpathogenic bacteria, but the organization of its machinery and basic function are still unknown. In this study, we identified a T3SS gene cluster from the plant growth-promoting Pseudomonas fluorescens 2P24 and isolated the corresponding T3SS apparatus. The T3SS gene cluster of strain 2P24 is similar organizationally to that of pathogenic P. syringae, except that it lacks the regulator hrpR and the hrpK1 and hrpH genes, which are involved in translocation of proteins. Electron microscopy revealed that the T3SS supramolecular structure of strain 2P24 was comprised of two distinctive substructures: a long extracellular, filamentous pilus and a membrane-embedded base. We show that strain 2P24 deploys a harpin homologue protein, RspZ1, to elicit a hypersensitive response when infiltrated into Nicotiana tabacum cv. xanthi leaves with protein that is partially purified, and by complementing the hrpZ1 mutation of pHIR11. The T3SS of strain 2P24 retained ability to secrete effectors, whereas its effector translocation activity appeared to be excessively lost. Mutation of the rscC gene from 2P24 T3SS abolished the secretion of effectors, but the general biocontrol properties were unaffected. Remarkably, strain 2P24 induced functional MAMP-triggered immunity that included a burst of reactive oxygen species, strong suppression of challenge cell death, and disease expansion, while it was not associated with the secretion functional T3SS.